THE INNER NATURE OF EDGAR ALLAN POE’S EXPRESSION TO THE SELECTED POEMS OF DREAM - sumardjo sumardjo (Prologue: Journal on Language and Literature, 2017)
This study aims to identify the depiction of the inner nature of dream’sexpression in Poe’s three selected poems to expose the dynamic vibration of desire, emotion, thought from the modification of mind. The perspective onthe omniscient narration of Poe’s is depicted to the three dream poemswithin which the inner nature of the character, including the past hopes,thoughts, feelings and the will to liberate the pain. The analysis adopts theauthorical voice models which operates the speaker within the literaryworks of dream theme. For Poe, The vision and the predicament of youngadulthood, and the dreams in the mid adult men should be a spirit guiding,the best learning of realities, and a lovely semblance of realities in theircoloring of life respectively. They should be deamed as the landscape of akind of huge spider-web of the expression within the finest silken threads ofthe will, desire, and thought. Poe was the opinion that the imaginary in themind of human being, the belief within the innermost of the heart, and theachievement toward any probabilities are the dynamic mind in motion liketraveling to the medium of an expression of the dream’s vision.